A Scoping Review of Research on Online Hate and Sport. (April 2023) - Kearns, Colm; Sinclair, Gary; Black, Jack; Doidge, Mark; Fletcher, Thomas; Kilvington, Daniel; Liston, Katie; Lynn, Theo; Rosati, Pierangelo
The rise of online hate speech in sports is a growing concern, with fans, players and officials subject to racist, sexist and homophobic abuse (in addition to many other prejudices) via social media platforms. While hate speech and discrimination have always been problems in sports, the growth of social media has seen them exacerbated exponentially. As a consequence, policy makers, sport governing bodies and grassroots anti-hate organisations are largely left playing catch-up with the rapidly shifting realm of online hate. Scholars have attempted to fill this vacuum with research into this topic, but such is the evolving nature of the issue that research has been diverse and fragmentary. We offer a scoping review into the scholarship of online hate in sport in order to encourage and facilitate further research into this urgent issue. Our review will achieve this through offering a comprehensive cataloguing of previously employed methodologies, case studies and conclusions. In doing so, it will not only equip future researchers with a concise overview of existing research in the field, but also illuminate areas and approaches in need of further examination.